2019
DOI: 10.4258/hir.2019.25.3.153
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Information System for Early Detection of Maternal Risk Factors Based on Continuum of Care Approach of Mother and Toddler Cohorts

Abstract: Objectives The aim of this study is to demonstrate how an integrated information system of mother and toddler cohorts can be developed as a basis of the continuum of care approach that subsequently can be used as the basis of early detection of risk factors of maternal mortality. Methods This research was carried out qualitatively. The data was collected through three techniques: in-depth interviews, focus group discussion, and document studies at six public health cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
(10 reference statements)
0
5
0
Order By: Relevance
“… 19 Moreover, the lack of health service utilization by pregnant mothers can result in unawareness of the risk of death either during pregnancy or childbirth. 20 , 21 Rizqi and Rubai reported that health service utilization should be considered because it is one of the determinants of receiving inappropriate care and diagnostic delays. 14 ‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬…”
Section: Introductionmentioning
confidence: 99%
“… 19 Moreover, the lack of health service utilization by pregnant mothers can result in unawareness of the risk of death either during pregnancy or childbirth. 20 , 21 Rizqi and Rubai reported that health service utilization should be considered because it is one of the determinants of receiving inappropriate care and diagnostic delays. 14 ‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬…”
Section: Introductionmentioning
confidence: 99%
“…Maternal health recording and reporting are still carried out in various documents using paper-based systems such as cohorts of pregnant women, childbirth, postpartum, family planning, and MCH books. Midwives find it difficult to ensure data accuracy because paperbased systems have a limited lifespan and usually collapse due to lack of space [4]. In addition, the mother's cohort column is also small, making writing difficult to read.…”
Section: Introductionmentioning
confidence: 99%
“…One of an attempt to make effective decision-making for delivery assistance for pregnant women and families is by increasing knowledge and awareness regarding the risks of pregnancy and childbirth. Lack of knowledge about health can have an impact on mortality during pregnancy and childbirth (Damayanti et al, 2019). Knowledge and awareness are not only fostered through formal education, but also obtained through attending associations, accessing the internet and other media such as TV, radio, posters, leaflets to get information directly through health workers.…”
Section: Introductionmentioning
confidence: 99%